2004
DOI: 10.1200/jco.2004.04.126
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of the Role of Positron Emission Tomography in the Management of Stage I and II Non-Small-Cell Lung Cancer

Abstract: For patients who are carefully and appropriately staged as having stage I-II disease, PET provides potential for more appropriate stage-specific therapy but may not lead to a significant reduction in the number of thoracotomies avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
1
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(89 citation statements)
references
References 16 publications
2
82
1
4
Order By: Relevance
“…The significant reduction in planned surgery with FDG-PET supports the cost-effectiveness and benefit to the patient of the approach. However, in a separate randomized, controlled trial in which advanced-stage cancer was rarely identified (2 cases among the 184 enrolled stage I-II patients), FDG-PET did not reduce unnecessary thoracotomies but did influence patient management (63). The prognostic significance of FDG-PET in NSCLC has also been established (64,65).…”
Section: Fdg-pet Validated For Staging and Diagnosis: A Biomarker Of mentioning
confidence: 99%
“…The significant reduction in planned surgery with FDG-PET supports the cost-effectiveness and benefit to the patient of the approach. However, in a separate randomized, controlled trial in which advanced-stage cancer was rarely identified (2 cases among the 184 enrolled stage I-II patients), FDG-PET did not reduce unnecessary thoracotomies but did influence patient management (63). The prognostic significance of FDG-PET in NSCLC has also been established (64,65).…”
Section: Fdg-pet Validated For Staging and Diagnosis: A Biomarker Of mentioning
confidence: 99%
“…Their results were different. Viney et al (20) have faced as primary result the performance of thoracotomy, which was performed in 98% of their patients of the CS group and in 96% of the group MS with FDG-PET besides CS (p = 0.44), and demonstrated that the addition of PET did not significantly reduce the number of thoracotomies. The main result of the study developed by van Tinteren et al…”
Section: Discussionmentioning
confidence: 99%
“…FDG PET/ BT görüntüleme uzak metastazların gösterilmesinde konvansiyonel tanısal incelemelerden daha başarılıdır (Şekil 2) (29,30,31,32,33,34,35 BT görüntülemenin ortalama duyarlılık ve özgüllük değerleri ise %93 ve %95 düzeyinde bulunmuştur (35). Uzak metastazların FDG PET/BT görüntüleme ile saptanması hastaların klinik evrelemesinde yaklaşık %20 oranında değişikliğe neden olur (32). Özet olarak, beyin metastazları dışında FDG PET/BT görüntüleme akciğer kanserinin uzak metastazlarını belirlemede yüksek duyarlılık ve özgüllük değerlerine sahiptir.…”
Section: Uzak Metastazların Gösterilmesiunclassified